Analysis of Net Stable Funding Ratio (NSFR) in the Banking Sector Listed on the Indonesian Stock Exchange (IDX) on Financial Performance for the Period 2018-2023 - Fauziah Ihsan; Rivani Rivani; Nurhana Dhea Parlina (Green Publisher Indonesia, 2025)
This study aims to analyze the effect of the Net Stable Funding Ratio on the financial performance of banks listed on the Indonesia Stock Exchange in the 2018–2023 period. Financial performance is measured using two main indicators, namely Return on Assets and Return on Equity. The Net Stable Funding Ratio is one of the liquidity ratios applied under Basel III to improve the stability of long-term banking funding. This study uses a quantitative method with a simple linear regression approach to test the effect of the Net Stable Funding Ratio on bank profitability (Return on Assets and Return on Equity). The results showed that the Net Stable Funding Ratio has no significant effect on ROA or ROE of the sample banks. The low R-squared value in both models indicates that the independent variable (NSFR) explains only a small part of the variation in the dependent variables (ROA and ROE), so other factors may be more influential in determining the company's profitability. The results are expected to provide insights for investors, regulators, and policymakers in understanding the relationship between funding stability and bank profitability, as well as serve as a reference in designing a more sustainable and competitive banking strategy in the financial market.